A method for preparing a non-wetting tantalate ceramic coating
Nano-scale tantalate powders were prepared by hydrothermal method and the coating was prepared by atmospheric plasma spraying technology, which solved the problems of pores and cracks in the ceramic coating and achieved efficient CMAS corrosion protection.
Patent Information
- Application Number
- CN202211460953.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-08
- Filing Date
- 2022-11-17
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-11-17
AI Technical Summary
There are microcracks and pores in existing ceramic coating materials, which leads to the coating being easily penetrated and corroded by CMAS melt in high temperature environments and fails.
Nano-scale tantalate RETaO4 powder was prepared by hydrothermal method, and a non-wetting tantalate ceramic coating was prepared by atmospheric plasma spraying technology to inhibit the formation of pores and cracks in the coating.
The prepared coating has high density and porosity less than 2%, which can effectively prevent CMAS melt penetration and improve the resistance to CMAS corrosion.
Smart Images

Figure CN115786840B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal barrier coatings, and in particular to a method for preparing a non-wetting tantalate ceramic coating. Background Art
[0002] Thermal barrier coatings are mainly used in the aviation engine industry. They mainly play the role of heat insulation, reducing the thermal mismatch between the coating and the alloy substrate, and effectively resisting particle impact to protect the high-temperature area components of the aviation engine. They are required to have good thermodynamic properties, such as low thermal conductivity, high thermal expansion coefficient and high temperature stability.
[0003] At present, the widely used thermal barrier coatings mainly include yttria-stabilized zirconia (YSZ) and rare earth zirconates (RE2Zr2O7), but both have certain shortcomings: YSZ has a low operating temperature (≤1200℃) and a relatively high thermal conductivity; while rare earth zirconates have a low thermal expansion coefficient, which has prompted researchers to look for thermal barrier coatings that can replace the above-mentioned ceramic materials. In 2007, Professor Clarke's research group at Harvard University and Professor Levi of the University of California, Santa Barbara proposed that yttrium tantalate (YTaO4) ferroelastics are expected to be used as a new type of thermal barrier coating material, but the research on rare earth tantalates mainly focuses on theoretical calculations of their crystal structure and luminescence properties. In 2016, Wang et al. prepared rare earth tantalate bulk materials by solid-phase reaction method and concluded that the thermal conductivity is much smaller than that of YSZ materials. The researchers' extensive research and experimental conclusions provide a theoretical basis for the application of rare earth tantalates in thermal barrier coatings.
[0004] The current preparation methods of ceramic powders (such as hydrothermal method, solid phase reaction method, etc.) cause certain microcracks and pores in the crystal structure of rare earth tantalate powders. When aircraft engines fly over harsh environments, such as over volcanic rocks, they will inhale certain sand, dust and fly ash from the airway. According to tests, the chemical composition of these silicate mineral particles is basically the same, mainly CaO, MgO, Al2O3, SiO2 and a small amount of Ni and Fe oxides, with a melting point of about 1200°C, collectively known as calcium-magnesium-alumino-silicate (CMAS). With the development of the aviation industry, the inlet temperature of the engine turbine is usually above 1200℃. At 1200℃, CMAS particles will melt, so CMAS particles are also called low-melting-point oxides. After melting, CMAS particles are deposited on the surface of the thermal barrier coating and "slowly" penetrate into the interior of the coating along the cracks in the coating. The brittle glass phase produced during the cooling process causes the strain tolerance of the coating to decrease, thereby causing the coating to delaminate and crack, and finally fail.
[0005] Therefore, how to prepare a non-wettable tantalate ceramic coating material that can effectively inhibit product pores and cracks in the coating and resist CMAS corrosion is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a non-wetting tantalate ceramic coating in view of the shortcomings of the prior art, so as to solve the problem of microcracks and pores in the tantalate ceramic coating in the prior art, which leads to delamination and cracking of the coating.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a non-wetting tantalate ceramic coating, comprising the following steps:
[0009] (1) mixing an aqueous solution of TaCl5 and an ethanol solution of RE(NO3)3 and heating them;
[0010] (2) during the heat preservation process, dilute ammonia water is added dropwise to keep the pH value of the solution between 6 and 8, and a gel colloid is obtained by reaction;
[0011] (3) calcining the obtained gel colloid to obtain nano-scale tantalate RETaO4 powder;
[0012] (4) Nano-scale tantalate RETaO4 powder is sprayed by atmospheric plasma to obtain a non-wetting tantalate ceramic coating material.
[0013] Preferably, the RE is Y, La, Nd, Sm, Eu, Gd, Dy, Ho, Er, Tm, Yb or Lu.
[0014] Preferably, the heating temperature in step (1) is 50-70°C.
[0015] Preferably, the concentration of the dilute ammonia water in step (2) is 9 to 11 g / mL; and the reaction time is 10 to 20 hours.
[0016] Preferably, in step (3), the colloid is washed with water and alcohol in sequence before calcination, and then dried at 90-110° C. for 10-20 hours.
[0017] Preferably, the calcination temperature in step (3) is 1200-1700° C. and the calcination time is 10-20 hours.
[0018] Preferably, the parameters of the atmospheric plasma spraying are: spray gun power of 35-42 kW, spray gun distance of 200-300 mm, gas flow rates of argon and hydrogen of 5-12 slpm and 5-12 slpm respectively, feed rate of 50-80 g / min, spray gun speed of 500-1000 mm / s, and spraying time of 2-5 min.
[0019] Beneficial effects of the present invention:
[0020] 1) The nano RETaO4 ceramic powder prepared by the hydrothermal method is spherical, and the particle size of the powder is 10 to 30 nanometers. The coating material can be directly prepared by atmospheric plasma spraying without other treatment;
[0021] 2) The grain size of the coating material prepared using nano-spherical powder is less than 1 micron, which can effectively inhibit the pores and cracks in the coating, so that the porosity of the coating is less than 2%, effectively preventing the CMAS melt from penetrating the coating through the pores and cracks at high temperature, and ensuring the integrity of the coating;
[0022] 3) RETaO4 itself is inert to react with CMAS melt. At the same time, the coating surface prepared by spraying nanopowders has small nano-scale protrusions, which greatly enhance the non-wettability between the ceramic coating and the CMAS melt, thereby effectively improving the fluidity of the CMAS melt on the coating surface, so that it does not react with the ceramic coating and flows away directly. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The XRD diagrams of the ceramic coatings prepared in Examples 1 to 5 and Comparative Examples 1 to 3 are shown.
[0024] Figure 2 The following are SEM images of the ceramic coatings prepared in Example 5 and Comparative Examples 1 to 3.
[0025] Figure 3 This is a real picture of the HoTaO4 ceramic coating prepared in Example 5 after the CMAS high temperature corrosion resistance experiment.
[0026] Figure 4 This is a real picture of the LuTaO4 ceramic coating prepared in Example 6 after the CMAS high temperature corrosion resistance experiment.
[0027] Figure 5 Comparison of the high temperature corrosion depth of rare earth tantalate RETaO4 ceramic CMAS prepared in Examples 1, 2 and 5 with that of Comparative Example 2. DETAILED DESCRIPTION
[0028] The present invention provides a method for preparing a non-wetting tantalate ceramic coating, comprising the following steps:
[0029] (1) mixing an aqueous solution of TaCl5 and an ethanol solution of RE(NO3)3 and heating them;
[0030] (2) during the heat preservation process, dilute ammonia water is added dropwise to keep the pH value of the solution between 6 and 8, and a gel colloid is obtained by reaction;
[0031] (3) calcining the obtained gel colloid to obtain nano-scale tantalate RETaO4 powder;
[0032] (4) Nano-scale tantalate RETaO4 powder is sprayed by atmospheric plasma to obtain a non-wetting tantalate ceramic coating material.
[0033] In the present invention, the RE is Y, La, Nd, Sm, Eu, Gd, Dy, Ho, Er, Tm, Yb or Lu.
[0034] In the present invention, the molar ratio of TaCl5 and RE(NO3)3 in step (1) is 1:1.
[0035] In the present invention, the concentration of the TaCl5 aqueous solution is 0.2-0.6 mol / L, preferably 0.3-0.5 mol / L; the concentration of the RE(NO3)3 ethanol solution is 0.2-0.6 mol / L, preferably 0.3-0.5 mol / L.
[0036] In the present invention, the heating temperature in step (1) is 50 to 70°C, preferably 55 to 65°C, and more preferably 57 to 63°C.
[0037] In the present invention, the concentration of the dilute ammonia water in step (2) is 9 to 11 g / mL, preferably 9.5 to 10.5 g / mL, and more preferably 10 g / mL; the reaction time is 10 to 20 hours, preferably 12 to 18 hours, and more preferably 13 to 15 hours.
[0038] In the present invention, during the heat preservation process, dilute ammonia water is added dropwise to keep the pH value of the solution between 6 and 8, preferably 7.
[0039] In the present invention, the colloid is washed twice with water and alcohol in sequence before calcination in step (3), and then dried at 90-110° C. for 10-20 hours.
[0040] In the present invention, the drying temperature is preferably 95 to 105° C., more preferably 98 to 103° C.; the drying time is preferably 12 to 18 hours, more preferably 13 to 17 hours.
[0041] In the present invention, the calcination treatment temperature in step (3) is 1200-1700° C. and the calcination time is 10-20 hours.
[0042] In the present invention, the calcination temperature is preferably 1300 to 1650° C., more preferably 1400 to 1600° C.; the calcination time is preferably 12 to 18 hours, more preferably 13 to 16 hours.
[0043] In the present invention, the parameters of the atmospheric plasma spraying are: the spray gun power is 35-42kW, the spray gun distance is 200-300mm, the gas flow rates of argon and hydrogen are independently 5-12slpm, the feed rate is 50-80g / min, the spray gun speed is 500-1000mm / s, and the spraying time is 2-5min.
[0044] In the present invention, the spray gun power is preferably 36-40 kW, and more preferably 38-39 kW.
[0045] In the present invention, the spray gun distance is preferably 210 to 290 mm, and more preferably 220 to 280 mm.
[0046] In the present invention, the gas flow rates of the argon gas and the hydrogen gas are independently 5 to 12 slpm, preferably 6 to 11 slpm, and more preferably 7 to 10 slpm.
[0047] In the present invention, the feed rate is preferably 55 to 75 g / min, more preferably 60 to 70 g / min.
[0048] In the present invention, the spray gun speed is preferably 600 to 900 mm / s, and more preferably 700 to 800 mm / s.
[0049] In the present invention, the spraying time is preferably 3 to 5 minutes, more preferably 4 minutes.
[0050] In the present invention, the nano-scale tantalate RETaO4 powder is a spherical powder with a particle diameter of 10 to 30 nanometers.
[0051] In the present invention, the porosity of the non-wetting tantalate ceramic coating is less than 2%, the coating is a layered structure, the grain size is less than 1 micron, and the surface has nano-scale protrusions, which can effectively increase the contact angle between the CMAS melt and the coating, thereby improving its anti-CMAS corrosion performance.
[0052] In the present invention, the non-wetting tantalate ceramic coating has a monoclinic crystal structure, a lattice space group of I2(5), and a density of the ceramic greater than 98%.
[0053] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0054] Example 1
[0055] Mix 0.5mol / L TaCl5 aqueous solution and 0.5mol / L Y(NO3)3 ethanol solution (control the molar ratio of TaCl5 and Y(NO3)3 to be 1:1), heat to 60℃ and stir continuously, add 10g / mL dilute ammonia water to keep the pH value of the solution at 6.5, and react for 15 hours to obtain a gel colloid. Wash the colloid once with water and then wash the colloid twice with alcohol, then place it in a box furnace at 100℃ for 12 hours, and finally calcine at 1200℃ for 20 hours to obtain nano-scale tantalate YTaO4 powder with a particle size of 10 nanometers;
[0056] The nano-scale tantalate powder was subjected to atmospheric plasma spraying, and the specific parameters were: spray gun power of 35 kW, spray gun distance of 200 mm, gas flow rates of argon and hydrogen of 6 slpm and 6 slpm respectively, feed rate of 55 g / min, spray gun speed of 500 mm / s, spraying time of 2 min, and the porosity of the obtained coating was 1.2%.
[0057] Example 2
[0058] Mix 0.2mol / L TaCl5 aqueous solution and 0.2mol / L La(NO3)3 ethanol solution (control the molar ratio of TaCl5 and La(NO3)3 to be 1:1), heat to 52℃ and stir continuously, add 9g / mL dilute ammonia water to keep the pH value of the solution at 6, and react for 11 hours to obtain a gel colloid. Wash the colloid once with water and then wash the colloid twice with alcohol, then place it in a box furnace at 103℃ for 12 hours, and finally calcine at 1700℃ for 10 hours to obtain nano-scale tantalate LaTaO4 powder with a particle size of 12 nanometers;
[0059] The nano-scale tantalate powder was subjected to atmospheric plasma spraying, and the specific parameters were: spray gun power of 42 kW, spray gun distance of 300 mm, gas flow rates of argon and hydrogen of 5 slpm and 7 slpm respectively, feed rate of 60 g / min, spray gun speed of 1000 mm / s, spraying time of 5 min, and the porosity of the obtained coating was 1.8%.
[0060] Example 3
[0061] Mix 0.6mol / L TaCl5 aqueous solution and 0.6mol / L Dy(NO3)3 ethanol solution (control the molar ratio of TaCl5 and Dy(NO3)3 to be 1:1), heat to 50℃ and keep shaking and stirring, add 11g / mL dilute ammonia water to keep the pH value of the solution at 7.1, and react for 12 hours to obtain a gel colloid. Wash the colloid once with water and then wash the colloid twice with alcohol, then place it in a box furnace at 90℃ for 13 hours, and finally calcine at 1500℃ for 15 hours to obtain nano-scale tantalate DyTaO4 powder with a particle size of 30 nanometers;
[0062] The nano-scale tantalate powder was subjected to atmospheric plasma spraying, and the specific parameters were: the spray gun power was 40kW, the spray gun distance was 240mm, the gas flow rates of argon and hydrogen were 11slpm and 9slpm respectively, the feed rate was 72g / min, the spray gun speed was 800mm / s, the spraying time was 3min, and the porosity of the obtained coating was 1.0%.
[0063] Example 4
[0064] Mix 0.35mol / L TaCl5 aqueous solution and 0.35mol / L Er(NO3)3 ethanol solution (control the molar ratio of TaCl5 and Er(NO3)3 to be 1:1), heat to 58℃ and stir continuously, add 10g / mL dilute ammonia water to keep the pH value of the solution at 8, and react for 20 hours to obtain a gel colloid. Wash the colloid once with water and then wash the colloid twice with alcohol, then place it in a box furnace at 93℃ for 18 hours, and finally calcine at 1350℃ for 12 hours to obtain nano-scale tantalate ErTaO4 powder with a particle size of 24 nanometers;
[0065] The nano-scale tantalate powder was subjected to atmospheric plasma spraying, and the specific parameters were: spray gun power of 38 kW, spray gun distance of 280 mm, gas flow rates of argon and hydrogen of 8 slpm and 8 slpm respectively, feed rate of 68 g / min, spray gun speed of 900 mm / s, spraying time of 4 min, and the porosity of the obtained coating was 0.5%.
[0066] Example 5
[0067] Mix 0.4 mol / L TaCl5 aqueous solution and 0.4 mol / L Ho(NO3)3 ethanol solution (control the molar ratio of TaCl5 and Ho(NO3)3 to be 1:1), heat to 70℃ and keep shaking and stirring, add 9.5 g / mL dilute ammonia water to keep the pH value of the solution at 6.3, and react for 16 hours to obtain a gel colloid. Wash the colloid once with water and then wash the colloid twice with alcohol, then place it in a box furnace and dry it at 105℃ for 15 hours, and finally calcine it at 1480℃ for 16 hours to obtain nano-scale tantalate HoTaO4 powder with a particle size of 18 nanometers;
[0068] The nano-scale tantalate powder was subjected to atmospheric plasma spraying, and the specific parameters were: spray gun power of 36 kW, spray gun distance of 260 mm, gas flow rates of argon and hydrogen of 6 slpm and 6 slpm respectively, feed rate of 62 g / min, spray gun speed of 680 mm / s, spraying time of 5 min, and the porosity of the obtained coating was 0.9%.
[0069] Example 6
[0070] Mix 0.5 mol / L TaCl5 aqueous solution and 0.5 mol / L Lu(NO3)3 ethanol solution (control the molar ratio of TaCl5 and Lu(NO3)3 to be 1:1), heat to 63°C and stir continuously, add 11 g / mL dilute ammonia water to keep the pH value of the solution at 7.5, and react for 13 hours to obtain a gel colloid. Wash the colloid once with water and then wash the colloid twice with alcohol, then place it in a box furnace and dry it at 100°C for 12 hours, and finally calcine it at 1620°C for 11 hours to obtain nano-scale tantalate LuTaO4 powder with a particle size of 21 nanometers;
[0071] The nano-scale tantalate powder was subjected to atmospheric plasma spraying, and the specific parameters were: spray gun power of 39 kW, spray gun distance of 220 mm, gas flow rates of argon and hydrogen of 6 slpm and 6 slpm respectively, feed rate of 55 g / min, spray gun speed of 720 mm / s, spraying time of 3 min, and the porosity of the obtained coating was 1.4%.
[0072] In order to study the influence of the above parameters on the performance of the ceramic coating, comparative experiments were conducted with the rare earth tantalate ceramics obtained in Comparative Examples 1 to 3 and the Examples:
[0073] The difference between Comparative Example 1 and Example 1 is that the sintering temperature is 1000° C., resulting in the prepared powder being a multi-phase mixture, not a single-phase YTaO4 ceramic, so it reacts with CMAS to cause the coating to be corroded and fail;
[0074] The difference between Comparative Example 2 and Example 1 is that a 10-50 micron powder prepared by high temperature sintering is used for spraying to prepare the coating, and the coating has a porosity of 10%. The large porosity causes the CMAS melt to directly penetrate into the coating through the pores, resulting in coating failure.
[0075] The difference between Comparative Example 3 and Example 1 is that the spray gun power is 20 kW, and the porosity of the prepared coating is 12%. The large porosity causes the CMAS melt to directly penetrate into the coating through the pores, resulting in coating failure.
[0076] The ceramic blocks obtained in Examples 1 to 6 and Comparative Examples 1 to 3 are tested:
[0077] 1. XRD characterization:
[0078] The ceramic blocks prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were tested using an X-ray diffractometer. The XRD patterns are as follows: Figure 1 As shown in the XRD test results of the rare earth tantalate ceramic samples obtained in Examples 1 to 5, the diffraction peaks correspond to the standard peaks of the standard PDF card #24-0478, and there is no second phase diffraction peak, indicating that the prepared samples are single-phase RETaO4 ceramics, and their crystal structure is monoclinic, wherein α=γ=90°, and β=95.5°, and the density is 9.71 g / cm 3 The lattice space group is I2(5), and XRD detection shows that no other impurities appear in the rare earth tantalate ceramic block. The diffraction peak of the obvious second phase Y3TaO7 in Comparative Example 1, while the others are all single-phase RETaO4 diffraction peaks.
[0079] 2. SEM characterization:
[0080] The ceramic blocks obtained in Example 5 and Comparative Examples 1 to 3 were examined using a scanning electron microscope. The SEM images are as follows: Figure 2 As shown, Figure 2 The SEM spectrum shows that the HoTaO4 ceramic sample is well crystallized, with uniform grain size and clear grain boundaries. No second phase is seen within or between the grains, which is consistent with the XRD results. Figure 2 There are no obvious pores and cracks in the rare earth tantalate (HoTaO4) ceramic block, indicating that the ceramic does not produce excessive pressure and stress during the sintering process, and the density is 99.1% through testing. The dark color in Comparative Example 1 is the second phase Y3TaO7 grains, indicating that the material phase is impure, making the material performance unstable; there are obvious pores in Comparative Examples 2 and 3, which can be penetrated and corroded by the CMAS solution, resulting in the failure of the coating material.
[0081] 3. Density detection:
[0082] The ceramic blocks obtained in Examples 1 to 6 and Comparative Examples 1 to 3 were measured using the Archimedean drainage method. It can be seen that the densities of the ceramic blocks obtained in Examples 1 to 6 are all greater than 98%.
[0083] 4. High temperature CMAS corrosion resistance experiment:
[0084] 4.1 CMAS preparation
[0085] Alumina (Al2O3), magnesium oxide (MgO), calcium oxide (CaO) and silicon oxide (SiO2) are mixed in a molar ratio of 15:19:22:44, and distilled water is added to grind and mix in a grinder to obtain uniform fine powder, wherein the grinder speed is 1000r / min and the grinding time is 20h; the ground powder is dried at 100°C for 10h, pre-calcined at 1000°C for 5h to obtain a block, and then the block is ground and passed through a 300-mesh sieve to obtain a uniform CMAS powder.
[0086] The CMAS powder prepared by the above method restores the CMAS component ratio in the front inlet of the engine turbine when the aircraft engine works in a harsh environment.
[0087] 4.2 Corrosion test
[0088] The CMAS powder was spread on the surface of the rare earth tantalate ceramic (RETaO4) block prepared in Examples 1 to 6, wherein the amount of CMAS powder was 15 mg / cm 2 , and then high-temperature sintering is carried out, the sintering temperature is 1200-1500°C, and the insulation time is 5-20h.
[0089] like Figure 3 This is a real picture of the rare earth tantalate (HoTaO4) ceramic prepared in Example 5 after sintering at 1300°C for 6 hours in the CMAS high temperature corrosion resistance experiment. Figure 4 This is a real picture of the rare earth tantalate (LuTaO4) ceramic prepared in Example 6 after sintering at 1500°C for 13 hours in the CMAS high temperature corrosion resistance experiment. After high temperature CMAS corrosion, it did not penetrate into the interior of the coating and remained on the surface of the coating, indicating that the coating material has excellent CMAS corrosion resistance.
[0090] Depend on Figure 5 It can be seen that under the same conditions, the corrosion depths of Examples 1, 2 and 5 prepared and used are all less than 10 microns, and a dense corrosion-resistant layer (dark gray) is formed between the surface CMAS layer (black) and the ceramic layer (light gray), while the corrosion depth in Comparative Example 2 reaches tens of microns, and at the same time, CMAS continuously penetrates inward along the pores, cracks and grain boundaries between the grains, causing the material to be completely corroded and fail.
[0091] Combination Figure 3 to Figure 5 It can be seen that there is still a large amount of CMAS powder on the surface of each ceramic sample, and the melting point of CMAS powder is lower than 1200℃. After being kept at high temperature (greater than 1200℃) for several hours, it still remains on the surface of RETaO4 ceramic coating, indicating that the CMAS molten liquid has not reacted with the RETaO4 ceramic material and is difficult to penetrate into the ceramic material, proving the excellent CMAS corrosion resistance of RETaO4 ceramic material. Under normal circumstances, other ceramic materials that are not resistant to CMAS corrosion, such as YSZ, will react with the CMAS molten liquid and penetrate into the interior of the ceramic after being kept at high temperature for several hours, and no CMAS powder will remain on the surface.
[0092] It can be seen from the above embodiments that the present invention provides a method for preparing a non-wetting tantalate ceramic coating. It can be seen from the test results that the rare earth tantalate (RETaO4) ceramic crystal structure prepared in embodiments 1 to 6 of the present invention has very few microcracks and pores, which makes it have a high density of more than 98%, and has good resistance to low melting point oxide corrosion. When the temperature reaches 1200 to 1500°C, the rare earth tantalate RETaO4 ceramic block hardly reacts with CMAS powder, and its high temperature CMAS corrosion resistance is much greater than that of YSZ.
[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a non-wetting tantalate ceramic coating, characterized in that: The following steps are involved: (1) mixing an aqueous solution of TaCl5 and an ethanol solution of RE(NO3)3 and heating them; (2) during the heat preservation process, dilute ammonia water is added dropwise to keep the pH value of the solution between 6 and 8, and a gel colloid is obtained by reaction; (3) calcining the obtained gel colloid to obtain nano-scale tantalate RETaO4 powder; (4) spraying nano-scale tantalate RETaO4 powder by atmospheric plasma to obtain a non-wetting tantalate ceramic coating material; The grain size of the non-wetting tantalate ceramic coating material is less than 1 micron; The heating temperature in step (1) is 50-70° C.; The concentration of the dilute ammonia water in the step (2) is 9 to 11 g / mL; and the reaction time is 10 to 20 hours.
2. The preparation method according to claim 1, characterized in that: The RE is Y, La, Nd, Sm, Eu, Gd, Dy, Ho, Er, Tm, Yb or Lu.
3. The preparation method according to claim 2, characterized in that: In the step (3), the colloid is washed with water and alcohol in sequence before calcination, and then dried at 90-110° C. for 10-20 hours.
4. The preparation method according to claim 1, 2 or 3, characterized in that: The calcination temperature in step (3) is 1200-1700° C. and the calcination time is 10-20 hours.
5. The preparation method according to claim 4, characterized in that: The parameters of the atmospheric plasma spraying are: spray gun power of 35-42 kW, spray gun distance of 200-300 mm, gas flow rates of argon and hydrogen of 5-12 slpm and 5-12 slpm respectively, feed rate of 50-80 g / min, spray gun speed of 500-1000 mm / s, and spraying time of 2-5 min.
Citation Information
Patent Citations
Non-wettability double-layer ceramic coating and preparation method thereof
CN114855121A
Tantalum and / or niobium based mixed oxide prepn.
FR2713218A1